1992
DOI: 10.1111/j.1365-2044.1992.tb03250.x
|View full text |Cite
|
Sign up to set email alerts
|

Vecuronium: an anthropometric comparison

Abstract: SummaryThis study set out to determine if there was any resistance to vecuronium in Nepalese studied in Nepal compared with Nepalese, Chinese and European patients studied in Hong Kong. The four groups, each of 10 male and 10 female patients, were intubated 60 s after administration of 0.1 mg.kg-' vecuronium. The Nepalese patients in Nepal had significantly less satisfactory intubating conditions ( p = 0.002). Similarly, male patients had significantly less satisfactory conditions than female patients ( p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Following administration of 0.1 mg kg -1 vecuronium, male patients had significantly less satisfactory intubation conditions at 60 s than female patients. It was suggested that diff erences in response to vecuronium could be explained by diff erences in distribution volume and muscle mass between sexes 14 . In another study, Xue et al 15 found that, compared to women, after intravenous administration, men had lower plasma concentrations of vecuronium and a larger volume of distribution of vecuronium.…”
Section: Discussionmentioning
confidence: 99%
“…Following administration of 0.1 mg kg -1 vecuronium, male patients had significantly less satisfactory intubation conditions at 60 s than female patients. It was suggested that diff erences in response to vecuronium could be explained by diff erences in distribution volume and muscle mass between sexes 14 . In another study, Xue et al 15 found that, compared to women, after intravenous administration, men had lower plasma concentrations of vecuronium and a larger volume of distribution of vecuronium.…”
Section: Discussionmentioning
confidence: 99%
“…The larger proportions of body fat in women may increase the body burden of lipidsoluble, slowly metabolized toxicants. Differences in body fat and in organ blood flow in women have been implicated in the faster onset of action and prolonged duration of neuromuscular blockade in women (e.g., vecuronium and rocuronium) [57, 58]. Differences in body fat content and in protein binding are responsible for sex-related pharmacokinetic differences in the distribution of diazepam (free fraction: in females 1.67% versus 1.46% in males).…”
Section: Sex Differences In Pharmacokineticsmentioning
confidence: 99%
“…Following administration of 0.1 mg kg 21 vecuronium, male patients had significantly less satisfactory intubation conditions at 60 s than female patients. It was suggested that differences in response to vecuronium could be explained by differences in distribution volume and muscle mass between sexes [16]. Semple and colleagues [17] demonstrated that females were significantly more sensitive to vecuronium than males, requiring 22% less drug to achieve the same degree of neuromuscular block.…”
Section: Discussionmentioning
confidence: 98%